Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:• The Social Intelligence Level of School Teachers in East Jerusalem: An Administrative Perspective from Principals and Vice PrincipalsMs. Rula Nemir Faries Ganem Khatib, Ms. Bayan Ali Muhammad Awar• The Predictive ability of Mindfullness in Burnout among inclusive schools Teachers in Alkarak GovernorateMs. Asmaa Abdelwahab Alkhtatnah, Asst-Prof. Mikail Ibrahim• Psychological Resilience and Its Relationship with Some 21st Century Skills Among Students of the Education Department at the University of NizwaAsst-Prof. Nasser Sulaiyam Almazidi , Asst-Prof. Khulood Ahmed Alobaidania• The Effectiveness of Rational Emotional Counseling Program in Reducing the Depressive Symptoms Among Retired Individuals in Salfeet GovernorateCo-Prof. Mona Abdel Qader Belbeisi, Mr. Alaa Abdel Hakim Muhammad Ibrahim• The Impact Level of Post-Traumatic Stress Disorder (PTSD) Symptoms on the Psychological  and Behavioral Health of Students at the University of Sharqiyah in the Sultanate of OmanDr. Khulood Ahmed Al-Obaidani, Ms. Khawla Salim Al-Habsi• The Sensorimotor Pathway to Musical Development in Early Childhood: Critical Theoretical Review of Educational Progress (2015–2025)Mr. Hassan Zrhida
Keywords: Journal of Educational and Psychological Sciences